An Autopsy Of The South Korean Market: Dynamics And Contradictions - Lee, You-Il (Asian Academy of Management (AAM), 2003)
The most dynamic feature of the South Korean economy in the late 20th century is the emergence of the country as a major destination for foreign investors. However, because the market has been closed to outsiders, for almost two decades, except for certain industries, Korea is as yet an unknown entity among the global business community. This acts as a deterrent to market entry. It is evident that among the economic and business literature there has been limited emphasis on the cultural and other complications such as the position and influence of the chaebol (a group of mostly family owned conglomerates in Korea) that exists for foreign businesses in the Republic of Korea. This paper attempts to crystallize some of the key cultural issues, examine their relevance and highlight some consequences of the lack of understanding of these cultural issues for the world's leading multinational corporations wishing to enter the Korean market.